2021
DOI: 10.1186/s12936-021-03677-3
|View full text |Cite
|
Sign up to set email alerts
|

Fitness characteristics of the malaria vector Anopheles funestus during an attempted laboratory colonization

Abstract: Background The malaria vector Anopheles funestus is increasingly recognized as a dominant vector of residual transmission in many African settings. Efforts to better understand its biology and control are significantly impeded by the difficulties of colonizing it under laboratory conditions. To identify key bottlenecks in colonization, this study compared the development and fitness characteristics of wild An. funestus from Tanzania (FUTAZ) and their F1 offspring during colonization attempts. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 70 publications
1
44
0
Order By: Relevance
“…funestus in laboratories is responsible for the more limited understanding of the biology of this species compared to other vector species. Recent evidence from attempted colonization in Tanzania has highlighted mating as one of the bottlenecks to colonization [45]. The ndings in this current study may therefore enable advancement towards alternative colonization processes either inside laboratories or by using semi-eld chambers and experimental huts in which natural mating can happen.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…funestus in laboratories is responsible for the more limited understanding of the biology of this species compared to other vector species. Recent evidence from attempted colonization in Tanzania has highlighted mating as one of the bottlenecks to colonization [45]. The ndings in this current study may therefore enable advancement towards alternative colonization processes either inside laboratories or by using semi-eld chambers and experimental huts in which natural mating can happen.…”
Section: Discussionmentioning
confidence: 74%
“…To our knowledge, only two strains have been successfully colonized from wild populations despite several attempts, both at the Vector Control Reference Laboratory (VCRL) in the National Institute for Communicable Diseases, South Africa, from populations in Angola (FANG) and Mozambique (FUMOZ) [44]. The FUMOZ strain also maintained at other laboratories worldwide including in Cameroon, UK [75] and Tanzania [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in Ulanga and Kilombero districts, have demonstrated that Anopheles funestus alone now contributes nearly nine in every ten new infections, even in villages where it is outnumbered by Anopheles arabiensis [6,23]. The species is also strongly resistant to pyrethroids used in the ITNs [24], survives much longer than its counterparts [6,25] and is strongly adapted to primarily bite humans over other vertebrates [26]. While no detailed analysis has been conducted, it is hypothesized that villages currently having the greatest malaria prevalence are those with highest densities of An.…”
Section: Introductionmentioning
confidence: 99%
“…funestus still remains the exception. This may in part simply reflect the logistical difficulty associated with rearing this species in the laboratory (Hunt et al 2005;Ngowo et al 2021;Morgan et al 2010), but may also reflect a quirk in its biology that make it more refractory to the process of germline transformation.…”
Section: Introductionmentioning
confidence: 99%